The nature and spatial variability of lowland savanna soils: Improving the resolution of soil properties to support land management policy. (14th May 2019) - Donoghue, Sarah; Furley, Peter A.; Stuart, Neil; Haggis, Robyn; Trevaskis, Alex; Lopez, German
Abstract: A fresh approach is presented to address the increasingly urgent need for alternative land management strategies in savannas. We illustrate how fine‐scale information of soil characteristics can be used to enable a more precise delimitation of sites suitable for different forms of land stewardship, including agro‐pastoral activities, forestry, biodiversity and tourism. By collating data from previous soil surveys, and augmenting this with targeted new surveys, we produce the first national data set of soil properties for the lowland savannas of Belize. Most of these soils are typical of savanna soils worldwide, that is acidic (mean surface pH = 5.7), nutrient‐poor (mean surface total exchangeable bases [TEB] = 3.4 cmol kg −1 ) and coarse‐textured (mean surface clay = 13.0%). Nevertheless, there is a marked spatial variability across the country in these soil properties. Some soils exhibit unusually high subsurface clay fractions (max = 73%), whilst other sites have exceptionally high pH in lower horizons (max = 8.4). Cluster analysis is used to group sites with similar soil properties. Across 79 sites, there is a clear division between soils with high clay percentages and those with coarser textures. These are sub‐divided into five groups based on further differences in parent material, chemical properties and site characteristics. Mapping the locations of these groups enables more specific land use recommendations to be made. This ability to make targeted land use recommendations from fine‐scale soil information represents an advance over the previous national land use policy, where all savanna lands were considered unsuitable for any form of agriculture. This approach could be applied to marginal savannas worldwide.